Evaluasi Pola Pengobatan Antihipertensi pada Pasien Hipertensi Rawat Jalan di Puskesmas Sumberlawang Sragen Tahun 2023 - Elira Dwi Ayu Erlandi; Hanugrah Ardya Crisdian Saraswati; Rolando Rahardjoputro (PPNI UNIMMAN, 2024)
Hypertension is a Non-Communicable Disease (NCD) characterized by elevated blood pressure above the normal value of 140/90 mmHg. Evaluation of antihypertensive drug use aims to ensure rational and effective medication use in hypertensive patients. Improper medication use can lead to treatment failure. The objective of this study is to evaluate the pattern of antihypertensive treatment among hypertensive outpatients at the Community Health Center (Puskesmas) of Sumberlawang Sub-District, Sragen in 2023. The research was descriptive observational with a cross-sectional study design. Sample selection used purposive sampling based on inclusion and exclusion criteria. The instrument for this study utilized medical records data of hypertensive outpatients at the Community Health Center (Puskesmas) Sumberlawang, Sragen from January to December 2023. Results from the study involving 100 hypertensive patients showed that the majority were female (78%), aged between 51-61 years (40%), with amlodipine being the most frequently used antihypertensive medication (62%), and Calcium Channel Blockers being the most commonly prescribed class of antihypertensive drugs (60%). Evaluation of antihypertensive treatment patterns among 100 patients revealed percentages indicating appropriate indication (100%), patient suitability (100%), correct drug selection (97%), and correct dosage (97%).